40. PSYCHOLOGICAL DISORDERS IN PATIENTS WITH MALIGNANT BLOOD DISEASE AT THE BLOOD TRANSFUSION HEMATOLOGY CENTER, BACH MAI HOSPITAL IN 2024 (Vietnam Journal of Community Medicine, 2024)
Objective: Describe the current state of anxiety, depression, and stress in patients with malignant blood diseases at the Hematology and Blood Transfusion Center of Bach Mai Hospital in 2024.Subjects and methods of research: A cross-sectional descriptive study was conducted on 390 patients at the Hematology and Blood Transfusion Center of Bach Mai Hospital from February 2024 to August 2024.Results: The proportion of patients in the study with anxiety disorders, depression, and stress was 46.2%, 38.5%, and 22.8%, respectively.Conclusions: The results showed that the rate of anxiety disorders, depression, and stress in patients was relatively high. Patients should be closely monitored for clinical symptoms and supported with palliative treatment.
Keywords: Psychological disorders; malignant blood diseases; anxiety; depression; stress